Analisis Sistem Penjaminan Mutu di Sekolah Dasar Berbasis Islamic Fullday School - Antariksa, Walid Fajar (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2019)
Primary school education must have good value and quality so that the next stage of the mission of national education can be continued. Primary school quality is influenced by how the school is managed. The purpose of this study is to analyze the quality assurance system in Islamic Fullday School-based elementary schools, especially regarding quality standards, implementations, and audits. This study uses qualitative research methods with a descriptive approach. This research was conducted at the Integrated Islamic Primary School (SDIT) Insan Permata Malang City. Data collection methods used are observation, interviews, and documentation. The results of this study indicate that the quality standards of graduates of SDIT Insan Permata Malang refer to two things, namely: First, Permendikbud No. 54 of 2013 concerning Competency Standards for Primary and Secondary Education Graduates. Secondly, SDIT Insan Permata Malang has internal standards that are unique in every education. The implementation of Quality Standards at SDIT Insan Permata is carried out by making work programs at the beginning of the year and then creating Standard Operating Procedures (SOP) for each activity. The Quality Audit at SDIT Insan Permata is carried out internally and externally. External audits are carried out by BAN-SM institutions as official institutions of the Government that are compulsory and carried out by the Kualita Pendidikan Indonesia (KPI) institution as a professional education management consulting institution. As for Internal Audit, SDIT Insan Permata does not yet have its quality assurance unit. Islamic Fullday School-based elementary schools should form an internal quality assurance unit to evaluate the application of quality standards in educational institutions. So that it can help and facilitate the school management and foundations to control and improve existing quality.